2017
DOI: 10.1111/1742-6723.12817
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and outcomes of missing admission medication history in severe trauma: A retrospective study

Abstract: Objective Anticoagulant and antiplatelet (ACAP) drugs are associated with increased mortality in trauma patients, therefore medication history on admission is important. Whether these medications are recorded on trauma admission has not been investigated, nor if absence of a medication history is associated with worse patient outcomes. Methods We conducted a retrospective database review combining demographic and outcome data from the St George Hospital (Sydney) trauma registry with admission medication histor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Miller et al sought to describe and compared three trauma groups from a level I trauma center in Sydney, Australia—those with medication histories currently on anticoagulants and antiplatelet medications (ACAP), those with medication histories not on ACAP, and those without medication histories [17]. Patient demographics, mechanism of injury, ISS, and clinical outcomes of these groups were compared.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Miller et al sought to describe and compared three trauma groups from a level I trauma center in Sydney, Australia—those with medication histories currently on anticoagulants and antiplatelet medications (ACAP), those with medication histories not on ACAP, and those without medication histories [17]. Patient demographics, mechanism of injury, ISS, and clinical outcomes of these groups were compared.…”
Section: Resultsmentioning
confidence: 99%
“…Congruence of anticoagulant medication lists determined by EMS or hospital providers was also low [24], and medications were frequently omitted or incomplete [18, 19]. Omissions were the most common medication errors [1719], totaling up to 72% in one article [19], consistent with the medication reconciliation reports in medicine patients [4]. Incomplete knowledge of medication usage and incorrect documentation by admitting clinicians contributed to medication reconciliation errors [18, 19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, the cases in the elderly group should be evaluated separately from the adult age group. The cases of the elderly age group are those in which cardiovascular diseases are frequent and antiaggregant, and in which anticoagulant drugs are used more frequently [11][12][13]. Therefore, in head trauma cases, it should be remembered that this age group is at higher risk regarding intracranial hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…Although the absence of a medication history was not associated with morbidity and mortality, the authors concluded that a more complex relationship might exist between patients, their mechanism of injury and medication history. 1 Engagement of a clinical pharmacist was a proposed option to improve admission medication histories in severe trauma. This conclusion is supported by a recent systematic review identifying involvement in severe trauma and resuscitation as a key emerging area of practice for Emergency Medicine (EM) clinical pharmacists.…”
mentioning
confidence: 99%